(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research proposes an innovation in the development of inkjet printing ink that uses black carbon pigment obtained from palm coconutshells. The main objective of this study was to look at thecharacterization of textile inkjet ink from the black carbon pigments of the palm coconut shell. The black carbon pigment produced from the coconut coat has been identified as the source of the pontentionalprinting ink of the textile fabric based on the polymer of acrylic styrene. The research method involves the extraction and purification of carbon pigments from palm coconut shells, as well as the formulation of inkjetprinting. The composition of the textile inkjet used in this study is that black carbon pigments come from palm coconut shells while the adhesives used are acrylic styrene, aquadest, potassium hydroxide (KOH), poly (natrium 4- styrenesulfonat). The research included the physical characteristics of the black carbon pigments produced and the evaluation of inkjet printing textiles using pigments. Textile inkjetcharacteristics. Results of ink testing using Binocular Microscope Scanbest sample CAST1. The results of ink pigment testing on wool fabrics and image analysis testing the lowest values are found on CAST1 sample. The result of the viscosity test that the ink viskosity value CAST1 of 13.1 is close to the value of commercial ink.